The hemostatic properties of chitosan in oral surgery - Franco, Rocco; Gianfreda, Francesco; Miranda, Michele; Barlattani, Alberta; Bollero, Patrizio (Biomedical and Biotechnology Research Journal, 2020)
Chitosan (CS) belongs to the natural linear aminopolysaccharide family. It is formed by a repetition of D-glucosamine units (deacetylated units) and a smaller number of N-acetyl-D-glucosamine units. Their distribution is casual. It derives from chitin which is a naturally occurring polysaccharide in the arthropod exoskeleton. CS is a biocompatible material and for this reason it is used in medicine, especially in dentistry. It also has anti-inflammatory and regenerative properties. It is used in conservative dentistry, periodontology, especially in oral surgery. Its antibacterial and hemostatic properties are useful in the surgical treatment of patients on anticoagulant/antiplatelet therapy. The purpose of this work is to analyze through a systematic review of the literature on the use of CS as a local hemostatic.